Gelation of Hole Transport Layer to Improve the Stability of Perovskite Solar Cells - Zhang, Ying; Zhou, Chenxiao; Lin, Lizhi; Pei, Fengtao; Xiao, Mengqi; Yang, Xiaoyan; Yuan, Guizhou; Zhu, Cheng; Chen, Yu; Chen, Qi (Nano-Micro Letters, 2023)
To achieve high power conversion efficiency (PCE) and long-term stability of perovskite solar cells (PSCs), a hole transport layer (HTL) with persistently high conductivity, good moisture/oxygen barrier ability, and adequate passivation capability is important. To achieve enough conductivity and effective hole extraction, spiro-OMeTAD, one of the most frequently used HTL in optoelectronic devices, often needs chemical doping with a lithium compound (LiTFSI). However, the lithium salt dopant induces crystallization and has a negative impact on the performance and lifetime of the device due to its hygroscopic nature. Here, we provide an easy method for creating a gel by mixing a natural small molecule additive (thioctic acid, TA) with spiro-OMeTAD. We discover that gelation effectively improves the compactness of resultant HTL and prevents moisture and oxygen infiltration. Moreover, the gelation of HTL improves not only the conductivity of spiro-OMeTAD, but also the operational robustness of the devices in the atmospheric environment. In addition, TA passivates the perovskite defects and facilitates the charge transfer from the perovskite layer to HTL. As a consequence, the optimized PSCs based on the gelated HTL exhibit an improved PCE (22.52%) with excellent device stability. Highlights: 1 The gelation of hole transport layer generates a dense and uniform hole transport layer film and significantly inhibits the aggregation of lithium bis(trifluoromethane sulfonyl)imide in spiro-OMeTAD. 2 The gelated hole transport layer confers enhanced charge carrier transport and better humidity and operational stability of perovskite solar cells.